Health Education Mentoring on Sadar Seimbang Nutrisi (SSN) and The Dangers of Anemia through Student Empowerment Movements with Examination of Hematology (Hemoglobin Hematocrit) in Vocational High School and Junior High School AsSyarief Garut for Mountainous Area Community (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Anemia in adolescent girls still shows a high prevalence rate. The prevalence of anemia in Indonesia at the age of 5-14 is 26.4%, 18.4% of patients aged 15-24 years, and women have a high risk of anemia, especially in adolescent girls. Adolescent girls with anemia will have changed the menstrual cycle. The importance of learning adolescent nutritional status will be strategic planning for decreased nutritional macro and micro deficiencies in women. This community dedication aimed to present information about the risk of anemia through student empowerment and hematological examination (hemoglobin-hematocrit). A piece of good and proper knowledge about balanced Nutrition is an essential point of anemia prevention in adolescents.